Efeito de uma sessão de tai chi chuan sobre o estado de humor em cuidadores de idosos que frequentam um ambulatório de fisioterapia: um estudo quase-experimental - Haidar, Aksis Medeiros (Universidade Federal de São Carlos, 2023)
Introduction: In a worldwide outlook, the elderly population is having a progressive increase, and this can lead to a greater need for people who take care of older adults population. Caregivers can be formal, who have a specific training and are stipendiary, or can be informal caregivers, who are usually family or close people. The act of caring can cause physical, emotional and psychological overload in caregivers, and Tai Chi Chuan is an integrative health practice that can be beneficial to the health of this population. Objective: to verify the effect of a single Tai Chi Chuan session on the mood state of formal or informal caregivers of the older adults who attend a physiotherapy ambulatory. Methods: This is a quasi-experimental study (CEP No. 5.443.848), held with 21 informal caregivers and 2 formal caregivers, with a total sample of 23 participants (54.04 ± 13.92 years of age). Caregivers were invited and voluntarily recruited at the “Unidade Sáude Escola (USE)” of the Federal University of São Carlos, where the older adults they cared for were performing physiotherapeutic treatment in various areas. For those who agreed to participate, a first session was held for anamense and assessment of the caregiver burden level measured using the Zarit scale and, in the second session the participant held a single session of 30-35 minutes of Tai Chi Chuan and the evaluation of the mood state measured with the Brunel scale, it was applied pre and post Tai Chi Chuan intervention. All evaluations were made at the USE of the Federal University of São Carlos. After normality analysis (Shapiro-Wilk) was used the paired T test for parametric data and Wilcoxon test for nonparametric data. The significance level adopted was p < 0.05. Results: The results showed that the levels of tension, depression, anger, fatigue and confusion showed significant differences after intervention (p <0.05), indicating an improvement in the mood state of these domains. The state of vigor did not show a significant difference, although it increased after the practice of Tai Chi Chuan. These results suggest that Tai Chi Chuan can be effective intervention to improve the mood of older adults caregivers. Conclusion: In conclusion, there was a positive effect of a single session of Tai Chi Chuan on the mood state of older adults caregivers who attended to a physiotherapy ambulatory, in the domains of tension, depression, anger, fatigue and confusion. The relevance of the findings for future studies and possible investments of the Unified Health System for the older adtuls caregiver population stands out.
Effect of a tai chi chuan session on the mood state of elderly caregivers attending a physiotherapy outpatient clinic: a quasi-experimental study
Keywords: Caregivers; Older adults; Mood state; Burden; Cuidadores; Idosos; Tai chi chuan; Estado de humor; Sobrecarga; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL